2021
DOI: 10.1371/journal.pone.0243688
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genetic diversity and population structure within Staphylococcus chromogenes by multilocus sequence typing

Abstract: Staphylococcus chromogenes is a common skin commensal in cattle and has been identified as a frequent cause of bovine mastitis and intramammary infections. We have developed a seven locus Multilocus Sequence Typing (MLST) scheme for typing S. chromogenes. Sequence-based typing systems, such as MLST, have application in studies of genetic diversity, population structure, and epidemiology, including studies of strain variation as a factor in pathogenicity or host adaptation. The S. chromogenes scheme was tested … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We noticed that strains associated with bovine mastitis clustered together as separate subclades in all the NASM genomes. Previous studies have reported that S. chromogenes ST-1 and ST-6 strains are associated with bovine mastitis (Huebner et al, 2021) (Persson Waller et al, 2023). Our observation also documents that S. chromogenes ST-1 and ST-6 are associated with bovine mastitis.…”
Section: Discussionsupporting
confidence: 86%
“…We noticed that strains associated with bovine mastitis clustered together as separate subclades in all the NASM genomes. Previous studies have reported that S. chromogenes ST-1 and ST-6 strains are associated with bovine mastitis (Huebner et al, 2021) (Persson Waller et al, 2023). Our observation also documents that S. chromogenes ST-1 and ST-6 are associated with bovine mastitis.…”
Section: Discussionsupporting
confidence: 86%
“…DNA was extracted from the first and last, when present, collected S. chromogenes isolate cultured from a quarter with a commercially available kit (DNeasy Blood and Tissue kit, Qiagen, Venlo, The Netherlands). The DNA was submitted to multilocus sequence typing (MLST) [42] to verify whether the recovered S. chromogenes isolates belonged to the same type as the inoculated S. chromogenes IM (ST 1). Four S. chromogenes isolates with a known sequence type (one ST1, two ST 44 and one ST 18) served as controls.…”
Section: Maldi-tof Mass Spectrometry and Multilocus Sequence Typingmentioning
confidence: 99%
“…Staphylococcus hyicus is the major causative agent of piglets’ exudative epidermitis [ 101 ]. Staphylococcus chromogenes has been identified as a frequent cause of bovine mastitis and intramammary infections [ 102 , 103 ]. Interestingly, colonization of mice with Staphylococcus epidermidis, a skin commensal bacteria producing 6-N-hydroxyaminopurine (6-HAP), has reduced the incidence of ultraviolet-induced tumours [ 10 ].…”
Section: Discussionmentioning
confidence: 99%